Preparation of High‐Grade Powders from Tomato Paste Using a Vacuum Foam Drying Method. Issue 8 (17th July 2015) - Sramek, Martin; Schweiggert, Ralf Martin; van Kampen, Andreas; Carle, Reinhold; Kohlus, Reinhard
Abstract We present a rapid and gentle drying method for the production of high‐grade tomato powders from double concentrated tomato paste, comparing results with powders obtained by foam mat air drying and freeze dried powders. The principle of this method consists of drying tomato paste in foamed state at low temperatures in vacuum. The formulations were dried at temperatures of 50, 60, and 70 °C and vacuum of 200 mbar. Foam stability was affected by low serum viscosity and the presence of solid particles in tomato paste. Consequently, serum viscosity was increased by maltodextrin addition, yielding optimum stability at tomato paste:maltodextrin ratio of 2.4:1 (w/w) in dry matter. Material foamability was improved by addition of 0.5% (w/w, fresh weight) egg white. Because of solid particles in tomato paste, foam air filling had to be limited to critical air volume fraction of Φ = 0.7. The paste was first pre‐foamed to Φ = 0.2 and subsequently expanded in vacuo. After drying to a moisture content of 5.6% to 7.5% wet base (w.b.), the materials obtained were in glassy state. Qualities of the resulting powders were compared with those produced by freeze and air drying. Total color changes were the least after vacuum drying, whereas air drying resulted in noticeable color changes. Vacuum foam drying at 50 °C led to insignificant carotenoid losses, being equivalent to the time‐consuming freeze drying method. In contrast, air drying caused lycopene and β‐carotene losses of 18% to 33% and 14% to 19% respectively. Thus, vacuum foam drying enables production of high‐grade tomato powders being qualitatively similar to powders obtained by freeze drying.